EU Regional Policy and Lisbon: Towards a new paradigm for regions after 2006 - Giordano, Benito (O Público e o Privado, 2020)
Much has been written about the role of regions in the EU, especially focusing upon the political and institutional challenges they face to increase their ‘voice’ at the European level. The conventional wisdom hitherto has been that those regions with greater legislative powers have been able to exert more influence on the European decision-making process. As this article argues, however, over the last couple of years, this conventional wisdom is being challenged because the political and institutional roles of the regions have become increasingly overshadowed by the economic imperative to increase regional competitiveness within the global economy. The EU’s Lisbon Agenda is the point of departure for this new phase, which is becoming more than simply a slogan; it is being translated into future EU funding and policy priorities. In particular, as this article explores, the EU’s ‘new’ Regional Policy after 2006 is a clear example of this shift in policy focus the implications of which remain to be seen.